PENGARUH PENGGUNAAN MEDIA SOSIAL INSTAGRAM TERHADAP GAYA HIDUP MAHASISWA - Putri Islamy; Hambali; Supentri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the development of information and communication technology in today's era. Social media is a medium that allows its users to interact virtually via internet connections. Currently, social media tends to be used to display excessive self-existence, which can ultimately influence mindsets, lifestyles, and even the culture of a nation. For students of the Pancasila Education and Citizenship Studies (PPKn) program at Riau University, social media not only serves as an interesting source of information but has also become a part of their daily lifestyle. This research aims to determine whether there is an influence of Instagram social media usage on the lifestyles of students in the Pancasila Education and Citizenship Studies (PPKn) program. This research employs a descriptive quantitative research method. The research population consists of all students of the PPKn Study Program at Riau University from the 2021, 2022, and 2023 cohorts. The research stages include the preparation of a questionnaire instrument, data collection from 70 students selected using purposive sampling techniques, and data analysis. Data analysis is performed using simple linear regression tests with the assistance of the Statistical Package for the Social Sciences (SPSS) version 25, after passing classical assumption tests (normality and linearity). The research results show that there is a positive and significant effect of Instagram social media use on the lifestyle of students. This is evidenced by a coefficient of determination (R²) value of 0.487, which means that the effect of the independent variable (Instagram Social Media) on the dependent variable (Lifestyle) is 48.7%.